The Influence of HbA1c and Gestational Weight Gain on Pregnancy Outcomes in Pregnant Women With Gestational Diabetes Mellitus - Zhang, Qiuhong; Lee, Chee Shin; Zhang, Lixia; Wu, Qi; Chen, Yunyan; Chen, Danqing; Qi, Lu; Liang, Zhaoxia (Frontiers in Medicine, 2022)
To investigate the influence of HbA1c level and GWG on pregnancy outcomes in pregnant women with GDM.2171 pregnant women with GDM was retrospectively included and categorized into: (1) normal(HbA1c<6%), elevated(HbA1c≥6%) HbA1c groups according to 2nd trimester HbA1c level; (2) inadequate, appropriate, and excessive GWG groups according to the IOM guidelines. In pregnant women with GDM, advanced age and high pre-pregnancy BMI were high risk factors for elevated HbA1c. Pregnant women with elevated HbA1c had higher OGTT levels than those with normal HbA1c, meanwhile the risks of adverse pregnancy outcomes were higher(P<0.05). The risks of primary caesarean section, hypertensive disorders during pregnancy and macrosomia of pregnant women with excessive GWG were significantly higher than those with inadequate and appropriate GWG(P<0.05). When GWG was appropriate, the risk of hypertensive disorders during pregnancy in the elevated HbA1c group was higher than that in the normal HbA1c group. When GWG was excessive, the risks of postpartum hemorrhage, macrosomia and neonatal asphyxia in the elevated HbA1c group were significantly higher than the normal HbA1c group(P<0.05).Monitoring and controlling blood glucose levels have shown effectiveness in reducing adverse pregnancy outcomes of women with GDM, especially for those who had excessive GWG.